Morphometric and Morphological Study of Mental Foramen in the Malaysian Population: Anatomy and Forensic Implications - Aspalilah Alias; AbdelNasser Ibrahim; Siti Noorain Abu Bakar; Mohamed Swarhib Shafie; Mohamed Swarhib Shafie; Faridah Mohd Nor (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/ Scopus